Systematic Review of Leadership Types Impacting Decision Support System Effectiveness Across Life Cycle Phases - Dillyana Handaru Kusuma Pratiwi; Sujoko (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
This study explores the influence of transformational, transactional, adaptive, and digital leadership on Decision Support System (DSS) effectiveness across its life cycle phases. Using a Systematic Literature Review (SLR) based on PRISMA guidelines, 25 articles from Scopus, Web of Science, and EBSCO databases were analyzed to examine leadership impact during DSS adoption, implementation, assimilation, and extension. The findings indicate that transformational leadership fosters innovation and acceptance in adoption, transactional leadership ensures compliance and stability in implementation, adaptive leadership enables flexibility in assimilation, and digital leadership drives continuous innovation in extension, enhancing overall DSS effectiveness. This study fills a critical gap in the literature by integrating traditional and emerging leadership perspectives to explain how leadership styles must evolve dynamically throughout the DSS life cycle. By integrating adaptive and digital leadership into traditional leadership frameworks, this study contributes to leadership and technology adoption research. Practically, the study guides organizational leaders, particularly in developing countries such as Indonesia, to align their leadership approaches with each DSS phase, enabling more effective digital transformation and sustained system utilization. It proposes a conceptual framework illustrating leadership's dynamic role in DSS phases and highlights the need for future empirical validation across various organizational contexts.